Amylose content and specific fine structures affect lamellar structure and digestibility of maize starches. (November 2020) - Zhong, Yuyue; Liu, Linsan; Qu, Jianzhou; Blennow, Andreas; Hansen, Aleksander Riise; Wu, Yuxin; Guo, Dongwei; Liu, Xingxun
Abstract: The molecular and lamellar structures and in vitro digestibility of high amylose maize starch granules were investigated. Size-exclusion chromatography (SEC) analysis of hydrodynamic radius ( R h ) and relative contents ( RC ) of different amylose and amylopectin pools revealed that increased amylose content resulted in the decrease of RC of short amylopectin chains (AP1, DP < 36), and the increase of R h and RC of long amylopectin chains (AP2, DP > 36). Fluorophore-assisted carbohydrate electrophoresis (FACE) analysis showed the average chain lengths of defined structures of fa, fb1, and fb3, and the content of fb3 were increased with the amylose content and at AC content of 43%, the chain lengths decreased with the amylose content. The relative contents of fa and fb1 and the degree of branching had the converse trends. Hence, HA-2, having an AC content of 43%, was the tipping point for these structural changes. Small angle X-ray scattering (SAXS) and its normalized 1D correlation function and SAXS scattering curve parametric fitting showed that the crystalline lamellar thickness was negatively correlated with proportion of short amylose chains (AM1, 100 <DP ≤ 150). The Bragg lamellar repeat distance was positively correlated to R h of the intermediate amylose chains (AM2, 150< DP ≤ 800). The amorphous lamellae thickness was positively correlated with the R h of long amylose chains (AM3, 800 <DP ≤ 40, 000). The positive correlation between R h of AM2 on the Gaussian peak area and the scattering invariant suggests AM2 chains stabilize the lamellar structure. Both the digestion rate of the digestible starch as well as the resistant starch content were positively correlated with amylose content. Pearson correlation analysis demonstrated that longer amylopectin chains and lower content of AP1 chains were positively correlated with the digestion rate. Graphical abstract: Image 1 Highlights: Structures and digestibility of maize starches as function of amylose content (AC) revealed specific relationships. AC 43% was the tipping point of amylopectin chain length distribution profiles. Starch granule lamellar structures were significantly correlated with amylose fine structure. The molecular size of AM2 was positively correlated with the ordering of the lamellar structure. Both the digestion rates of the digestible part and resistant starch content increased with AC.